RELATIONSHIP BETWEEN PERSONAL HYGIENE AND BASIC SANITATION WITH SKIN DISEASES IN CHILDREN AT JUKING PAJANG 1 ELEMENTARY SCHOOL: JUKING PAJANG VILLAGE MURUNG RAYA REGENCY IN 2025 - Lingmiona Lingmiona; Juanda Juanda; Arifin Arifin; Yohanes Joko Supriyadi (Jurnal Skala Kesehatan, 2026)
Abstract Personal hygiene and basic sanitation are fundamental requirements for maintaining health and preventing disease transmission. Poor implementation of these practices is strongly associated with skin conditions. This study aimed to investigate the correlation between personal hygiene, basic sanitation, and skin disease prevalence among students at SDN Juking Pajang 1. This quantitative study employed a cross-sectional design with 55 respondents selected via Simple Random Sampling. Data were analyzed using the Chi-Square test (Î±=0.05). The analysis revealed a significant relationship between personal hygiene and skin disease (p=0.013), with an Odds Ratio (OR) of 12.000, indicating that students with poor hygiene are 12 times more likely to suffer from skin diseases. Similarly, basic sanitation showed a significant correlation (p=0.008), with an OR of 6.923, suggesting that poor sanitation increases the risk of skin disease by approximately 6.9 times. Schools are advised to implement interactive health education and routine hygiene inspections. Students should practice consistent hygiene habits with parental supervision. Furthermore, local policymakers must intervene to improve basic sanitation infrastructure, particularly regarding household waste and wastewater management. Keywords: Personal Hygiene, Skin Diseases, and Basic Sanitation